Analysis of the development model for the microteaching laboratory to effectively train qualified teachers - Toto Fathoni; Rudi Susilana; Nandang Budiman; Badru Zaman; Effy Mulyasari; Budi Setiawan; Della Amelia; Ikmal Redzuan (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2024)
This study aims to develop an effective microteaching laboratory model in preparing superior prospective teachers. This study was conducted through a series of stages, including needs analysis, model design, implementation, evaluation, and refinement. Needs analysis was conducted to understand the needs and expectations of microteaching course lecturers and prospective teachers regarding the microteaching practice experience. The design of the microteaching laboratory model involved the development of infrastructure, curriculum, guidelines, and supporting implementation procedures. The implementation of the model was carried out by involving course lecturers and prospective teachers in a structured microteaching practice implementation session. Evaluation was conducted to evaluate the effectiveness of the model based on predetermined criteria. Refinement was carried out to improve and enhance the model based on evaluation findings and to prepare prospective teachers well through structured simulation, reflection, and feedback experiences. The implication of this study is the importance of developing a learning model that is in accordance with the needs of prospective teachers to produce superior graduates in the education profession. The results of the study indicate that the development of a microteaching laboratory can improve the teaching skills of prospective teachers through simulation, reflection, and feedback provided in an environment that supports learning. The implication of this study is the importance of developing learning facilities and infrastructure that are in accordance with the needs of prospective teachers in developing their teaching skills.